METHODOLOGY FOR THE ASSESSMENT OF TRANSFORMATION OF POLITICAL AND ECONOMIC SYSTEMS OF THE STATE UNDER THE CONTEXT OF GLOBALIZATIONS - Kozlov, Serguei D.; Slobotchikov, Oleg, N.; Shatokhin, Mikhail V.; Zaitseva, Natalia A.; Udovik, Elena E.; Artemova, Elena I.; Syanov, Dmitry A. (International Journal of Psychosocial Rehabilitation, 2020)
In the context of an increasing global world order, there is a need to create a relatively universal methodology that allows with a certain degree of certainty to assess the state’s position in it, taking into account the level of development of national political and economic systems. The purpose of this study is to develop a methodology for assessing the transformation of the political and economic systems of the state in the context of globalization. The use of the national competitiveness index is proposed as a universal indicator for assessing transformation processes in this area of research. The author substantiates the relevance of the formation of a statistical-analytical apparatus for assessing the national competitiveness of the state, taking into account the index approach. A model which is presented in the work, allows one to identify patterns of transformation of the country’s political and economic systems based on a synthesis of the existing challenges of the global world, the most relevant of which are economic growth, the level of human potential development, e-government, and the degree of democratization of the political regime. The developed author’s model for assessing the transformation of political and economic processes is of a universal methodological nature and can be used for various national formations. The use of the index method creates the prerequisites for identifying trends in the development of the studied phenomena in the medium term. As a practical adaptation of the proposed methodology, the author performed a situational analysis of the results of applying the model of national competitiveness in the context of globalization based on the use of the method of selective observation.